1998
DOI: 10.1038/sj.bjc.6690022
|View full text |Cite
|
Sign up to set email alerts
|

Deletions of the region 17p11-13 in advanced melanoma revealed by cytogenetic analysis and fluorescence in situ hybridization

Abstract: Malignant melanoma (MM) is a common cancer amongCaucasians and has shown a deplorable increase in incidence rates during recent decades. Early diagnosis -and consequently early surgical excision -has been greatly improved, leading to an average 5-year survival rate of up to 80%. Therefore, stable incident death rates of MM could be observed. However, the prognosis of metastatic MM still remains poor, with a long-term survival rate of about 20% in stage III patients (Balch et al, 1992;Johnson et al, 1995).Cytog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…1a ) ( Jonsson et al, 2007 ; Roschke et al, 2003 ; Spivey et al, 2012 ; Thompson et al, 1995 ). Also, at the individual gene level, most genes were affected by copy number gains and losses in accordance with others’ reports ( Grafstrom et al, 2005 ; Jonsson et al, 2007 ; Okamoto et al, 1999 ; Pirker et al, 2003 ; Shi et al, 2012 ) ( Fig. 1b , see full data set in Table S2 ).…”
Section: Resultssupporting
confidence: 91%
“…1a ) ( Jonsson et al, 2007 ; Roschke et al, 2003 ; Spivey et al, 2012 ; Thompson et al, 1995 ). Also, at the individual gene level, most genes were affected by copy number gains and losses in accordance with others’ reports ( Grafstrom et al, 2005 ; Jonsson et al, 2007 ; Okamoto et al, 1999 ; Pirker et al, 2003 ; Shi et al, 2012 ) ( Fig. 1b , see full data set in Table S2 ).…”
Section: Resultssupporting
confidence: 91%
“…In 1998, Park et al [35] found allelic loss in DN but not in BN. In 1999, Okamoto et al [36] reported deletions in the 17p13 region in melanomas ( fig. 1, table 2).…”
Section: Karyotypic Abnormalities and Allelic Loss At The Tp53 Gene Lmentioning
confidence: 99%